Reinterpretation Of Asbāb Wurūd Al-Ḥadīth (Analysis of Socio-Cultural Approach and Its Implementation in the Cultural Context of Indonesia) - Alwi Shobri; Fahrur Razi; Ananda Prayogi (Journal of Islamic Civilization, 2024)
This article examines the understanding of Asbāb Wurūd al-Ḥadīth through a socio-cultural approach and its application within the Indonesian cultural context. The reinterpretation of hadiths with asbāb al-wurūd must always consider historical, social, and cultural factors to reveal the underlying contexts, whether they involve questions posed to the Prophet Muhammad or other circumstances. This study emphasizes the importance of investigating hadiths through a socio-cultural lens for a more comprehensive and contextual analysis. The research aims to uncover various implicit meanings embedded within the social, cultural, and traditional dimensions of the hadith, providing broader insights into their relevance and applicability in different cultural settings, particularly within Indonesia. Conceptually, this research is a literature review employing qualitative methods. The analysis utilizes descriptive techniques alongside a contextual approach developed by John Dewey, which focuses on situational and environmental factors influencing hadith transmission. The key findings of the study include the identification of several hadiths analyzed through socio-cultural dimensions that can be applied within the Indonesian cultural framework. These examples include: (1) the hadith about wearing sandals during prayer (social aspect), (2) the hadith about wearing a turban (cultural aspect), (3) the hadith about women’s leadership (political aspect), and (4) the hadith regarding the command to bathe on Fridays (economic aspect). In conclusion, the socio-cultural approach offers a significant contribution to contextualizing hadiths and adapting them to the unique cultural conditions in Indonesia, enhancing their relevance and applicability in modern society.